2018
DOI: 10.1016/j.addr.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of statins via inhalation to treat lung inflammatory conditions

Abstract: Despite many therapeutic advancements over the past decade, the continued rise in chronic inflammatory lung diseases incidence has driven the need to identify and develop new therapeutic strategies, with superior efficacy to treat these diseases. Statins are one class of drug that could potentially be repurposed as an alternative treatment for chronic lung diseases. They are currently used to treat hypercholesterolemia by inhibiting the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, that catalyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 181 publications
(163 reference statements)
0
18
0
Order By: Relevance
“…Hence, alternative routes of statin administration are warranted to improve its efficacy. The repurposing of statins, as an inhaled therapy, is one such strategy as it delivers higher concentrations of drug to the lungs at lower drug dosages as compared to oral delivery 62, 63. There are increasing lines of evidence showing the potential and benefits of using inhaled statins in mouse models with inflammatory lung diseases 64-66.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, alternative routes of statin administration are warranted to improve its efficacy. The repurposing of statins, as an inhaled therapy, is one such strategy as it delivers higher concentrations of drug to the lungs at lower drug dosages as compared to oral delivery 62, 63. There are increasing lines of evidence showing the potential and benefits of using inhaled statins in mouse models with inflammatory lung diseases 64-66.…”
Section: Discussionmentioning
confidence: 99%
“…In several animal experiments, the inhalation of statins such as simvastatin pravastatin, rosuvastatin, pitavastatin, and atorvastatin induced better effects on anti-pulmonary inflammation. 232 Thus, statins could be efficacious in the treatment of lung inflammatory disorders and the development of inhalation formulations is warranted.…”
Section: Journal Of Inflammation Research 2021:14mentioning
confidence: 99%
“…Since hyperlipidemia is an independent risk factor for CVD, and since many patients with COPD die of CVDs, statins could have benefit in reducing mortality. Some authors suggest that statins, in addition to decreasing of serum cholesterol, may have anti-inflammatory effects on both pulmonary and systemic inflammation through inhibition of guanosine triphosphates and nuclear factor-κB that controls activation of inflammatory and matrix remodeling pathways (110). A meta-analysis of 15 articles with a total of 238,459 participants with COPD found that the use of statins was associated with a 31% reduced risk of MI (HR 0.69, 95% CI 0.49–0.99), but not of CVD mortality (111).…”
Section: Medication Issuesmentioning
confidence: 99%